Shophouses Façade Typology on Corridor of Gagak Hitam and A.H. Nasution Street (International Journal of Architecture and Urbanism, 2023)
The façade as a representative element of an architectural work can be an indicator of environmental character apart from socio-cultural, spiritual, and economic conditions at a certain time. The emergence of new buildings in the city of Medan is facing a rapidly changing face of the city, accompanied by the increasing need for space utilization and variations in building façade designs, where this phenomenon occurs in outer ring roads. Gagak Hitam and A.H. Nasution street, as the outer ring road of the city of Medan, is growing rapidly with various types of functions with the dominance of modern shophouses, which produce a façade typology that can be grouped and looked for differences according to certain indicators in the existing theory review. This study aimed to find a typology of shophouse façades in the corridor of Gagak Hitam and A.H. Nasution street, which became their character. The researcher collected data from literature sources, observed the research area, and redrawn the two-dimensional façade model to identify, in general, the elements and composition of the façade of the research object. According to the findings, there is no special type that becomes the standard for the character of the shophouses in the two road corridors.